Bacteriophage Therapy of Chronic Nonhealing Wound: Clinical Study. (June 2019) - Gupta, Pooja; Singh, Hari Shankar; Shukla, Vijay K.; Nath, Gopal; Bhartiya, Satyanam Kumar
Background: A chronic wound usually results due to halt in the inflammatory phase of wound healing. Bacterial infections and biofilm formation are considered to be the basic cause of it. Chronic wounds significantly impair the quality of life. Antibiotics are now failing due to biofilm formation emergence of drug-resistant bacteria. Objective: This study aims to see the effect of bacteriophage therapy in chronic nonhealing wound infected with the following bacteria: Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa . Subject: Patients with chronic nonhealing wound not responding to conventional local debridement and antibiotic therapy were included in the study. The age of patients ranged between 12 and 60 years. Method: A total of 20 patients selected and tissue biopsies and wound swabs were taken for isolation of the bacteria. After confirmation of organism, a cocktail of customized bacteriophages was topically applied over the wound on alternate days till the wound surface became microbiologically sterile. Mean bacterial count and clinical assessment were done and compared at the time of presentation and after 3 and 5 doses of application. Results: A significant improvement was observed in the wound healing, and there were no signs of infection clinically and microbiologically after 3 to 5 doses of topical bacteriophage therapy. Seven patients achieved complete healing on day21 during follow up while in others healthy margins and healthy granulation tissue were observed. Conclusion: Topical bacteriophage application may be quite effective therapy for the treatment of chronic nonhealing wounds.